Colombia : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2018)
This fiscal transparency evaluation (FTE) report assesses fiscal transparency practices in Colombia against the first three pillars of the IMF's Fiscal Transparency Code. Fiscal forecasting and budgeting-Pillar II-is the strongest area in Colombia's FTE. Half of the related indicators are advanced, mostly in the areas of: (1) orderliness of the legislative process and the adequacy of powers and information available to Congress; (2) credibility of economic and fiscal forecasts; and (3) medium-term forecasts and policy orientation. Fiscal reporting-Pillar I-and fiscal risk analysis and management-Pillar III-also reveal clear strengths. Fiscal reporting practices are advanced in terms of the coverage of fiscal institutions in fiscal reports and timeliness of annual financial statements.